In-situ forming dynamic covalently crosslinked nanofibers with one-pot closed-loop recyclability - Wang, Sheng; Wang, Nannan; Kai, Dan; Li, Bofan; Wu, Jing; YEO, Jayven Chee Chuan; Xu, Xiwei; Zhu, Jin; Loh, Xian Jun; Hadjichristidis, Nikos; Li, Zibiao (Nature communications, 2023)
Polymeric nanofibers are attractive nanomaterials owing to their high surface-area-to-volume ratio and superior flexibility. However, a difficult choice between durability and recyclability continues to hamper efforts to design new polymeric nanofibers. Herein, we integrate the concept of covalent adaptable networks (CANs) to produce a class of nanofibers ⎯ referred to dynamic covalently crosslinked nanofibers (DCCNFs) via electrospinning systems with viscosity modulation and in-situ crosslinking. The developed DCCNFs possess homogeneous morphology, flexibility, mechanical robustness, and creep resistance, as well as good thermal and solvent stability. Moreover, to solve the inevitable issues of performance degradation and crack of nanofibrous membranes, DCCNF membranes can be one-pot closed-loop recycled or welded through thermal-reversible Diels-Alder reaction. This study may unlock strategies to fabricate the next generation nanofibers with recyclable features and consistently high performance via dynamic covalent chemistry for intelligent and sustainable applications. Polymeric nanofibers are attractive nanomaterials owing to their high surfacearea- to-volume ratio and superior flexibility but designing durable and recyclable polymer nanofibers is challenging. Here, the authors integrate the concept of covalent adaptable networks to produce dynamic covalently crosslinked nanofibers via electrospinning.